2009
DOI: 10.1007/s00134-009-1422-7
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative validation of a new system for invasive continuous cardiac output measurement

Abstract: Although TruCCOMS may significantly underestimate CO, measurement trends correlate with TTFM. For this reason, a negative trend in RV output should trigger more specific diagnostic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…TTFM reliably detects portal venous and arterial blood flow after the reperfusion of hepatic grafts. Previous studies have indicated that this method generates reproducible and valid data 16‐18, 24. Therefore, the aim of the present study was to determine the effects of portal venous, arterial, and total blood flow on postoperative organ function, complication rates, and graft survival.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…TTFM reliably detects portal venous and arterial blood flow after the reperfusion of hepatic grafts. Previous studies have indicated that this method generates reproducible and valid data 16‐18, 24. Therefore, the aim of the present study was to determine the effects of portal venous, arterial, and total blood flow on postoperative organ function, complication rates, and graft survival.…”
Section: Discussionmentioning
confidence: 96%
“…Portal and hepatic blood flow was measured with TTFM at the end of the surgery (Medi‐Stim AS, Oslo, Norway). This method generates valid data and provides reliable measurements that are independent of the examiner's experience as well as environmental conditions that cannot be controlled, such as the measurement angle, blood temperature, and hematocrit level 16‐18…”
Section: Methodsmentioning
confidence: 99%
“…Dancona et al [28] tested a continuous cardiac output (CO) recording system that operates on the thermal conservation principle, and they compared it with the reference standard transit time flow measurement. There was a significant underestimation of CO with the continuously recording system, but it may be useful to detect trends over time.…”
Section: Devices and Techniquesmentioning
confidence: 99%
“…The measurement of intraoperative blood flow was performed with a flow metre VeriQ, based on measuring the transit time (MFTT) and Doppler technology. This system has been validated in previous studies and generates reproducible measurements[20-22].…”
Section: Discussionmentioning
confidence: 99%